2012
DOI: 10.1044/1092-4388(2012/10-0153)
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Environmental, and Linguistic Predictors of Syntax in Fragile X Syndrome and Down Syndrome

Abstract: Purpose We examined which cognitive, environmental, and speech/language variables predict expressive syntax in boys with fragile X syndrome (FXS), Down syndrome (DS), and typical development (TD), and whether predictive relationships differed by group. Method We obtained Index of Productive Syntax scores for 18 boys with FXS only, 20 boys with both FXS and autism spectrum disorder, 27 boys with DS, and 25 younger TD boys of similar nonverbal mental age (MA). Predictors included group (diagnosis), nonverbal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 94 publications
0
28
0
1
Order By: Relevance
“…Nonverbal cognition and phonological working memory are other key factors that play a role in syntactic ability. 63 …”
Section: Resultsmentioning
confidence: 99%
“…Nonverbal cognition and phonological working memory are other key factors that play a role in syntactic ability. 63 …”
Section: Resultsmentioning
confidence: 99%
“…These measuresdistinguish language-typical from language-disordered populations (27) and evidence is accumulating that these measures can distinguish individuals with FXS from those with other neurodevelopmental disorders, such as Down syndrome (13,22,2831). Guidelines for standardization for a number of language sampling procedures (e.g., conversation, narration) exist (32), and these procedures can be mastered with rather minimal training (26).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, future studies should examine the effect of lower intelligibility measured independently of articulatory skill. Estigarribia (2010) presented data showing approximately 60% of the variance in syntax scores in three groups (TD, FXS, and Down's syndrome) is attributable to diagnostic group, cognitive measures (including phonological working memory), and speech intelligibility, but that the remaining 40% is possibly specifically syntactic.…”
Section: Discussionmentioning
confidence: 99%
“…(Even though Roberts et al (2007a) found that intelligibility was not a significant predictor of syntactic skill in FXS.) Estigarribia (2010) presented a model including putative predictors of syntax in these populations that begins to address the important issue of within‐group variability.…”
Section: Discussionmentioning
confidence: 99%